Chemical diversity in Lippia alba (Mill.) N.E. Brown germplasm - Blank, Arie Fitzgerald (2016)
The aim of this study was to perform chemical characterization of Lippia alba accessions from the Active Germplasm Bank of the Federal University of Sergipe. A randomized block experimental design with two replications was applied. The analysis of the chemical composition of the essential oils was conducted using a gas chromatograph coupled to a mass spectrometer. The chemical composition of the essential oils allowed the accessions to be allocated to the following six groups: group 1: linalool, 1,8-cineole, and caryophyllene oxide; group 2: linalool, geranial, neral, 1,8-cineol, and caryophyllene oxide; group 3: limonene, carvone, and sabinene; group 4: carvone, limonene, g-muurolene, and myrcene; group 5: neral, geranial, and caryophyllene oxide; and group 6: geranial, neral, o-cymene, limonene, and caryophyllene oxide.